Demonstration of high separation efficiency for polystyrene-modified sub-1 µm particles originating from silica monolith under isocratic elution mode in liquid chromatography. Issue 19 (14th December 2019) - Ali, Faiz; Malik, Aamra Rafique; Cheong, Won Jo; Rehman, Najeeb-UR-
Abstract: Renovated protocols for the synthesis and modification of sub-1 µm porous particles originating from silica monolith coupled with sophisticated packing procedures have made it possible to get excellent separation efficiency and the possibility for rapid analysis when dealing with five benzene derivatives in high-performance liquid chromatography. The catalyst-assisted binding of 4-chloromethylphenyl-isocynate and consequent reversible addition-fragmentation chain transfer (RAFT) polymerization enabled the attachment of uniform polymer film onto the silica particles. The column (1.0 mm ID × 300 mm length) packed with such particles resulted in supreme separation efficiency (256, 200 plates/m) which is comparable to the separation efficiency of column packed with core shell particles. The optimum separation was obtained in 65/35 (v/v %) acetonitrile/water with 0.1% trifluoroacetic acid at a flow rate of 28 µL/min. Particle size reduction with increased pore size along with sophisticated packing protocol, partial monolithic architecture of the packed bed, and uniformly distributed polymer film are the beneficial features responsible for the improved chromatographic performance of the final stationary phase. GRAPHICAL ABSTRACT: